CLINICAL OUTCOME OF GUILLAIN BARRE SYNDROME IN THE INTENSIVE CARE UNIT OF A PEDIATRIC TERTIARY CARE HOSPITAL - AMIN , W; ARSHAD , S; IQBAL , S; AHMED , A; AWAN, MSBF (Biological and Clinical Sciences Research Journal, 2023)
Since poliomyelitis was eradicated, Guillain-Barre syndrome has been the leading cause of acute flaccid paralysis globally. Critical care and mechanical breathing may be necessary in extreme circumstances. Among paediatric patients hospitalized in the intensive care unit of a Karachi tertiary hospital, we aimed to quantify the incidence of Guillain-Barré Syndrome clinical outcomes. Cardiology Intensive Care Unit (NICH) in Karachi, Pakistan. January 9, 2020, to July 10, 2020—six months. Children admitted to the intensive care unit at NICH with GBS, as defined operationally, ranging in age from six months to twelve years, were included in the study. They stimulated the posterior tibial nerve (PTN) and common peroneal nerve (CPN), allowing for studying motor nerve conduction and using the median and ulnar nerves to measure compound muscle action potentials' onset delay, amplitude and conduction velocity (CMAPs). Research on the conduction of sensory nerves was carried out to quantify SNAPs in the sural, median, and ulnar regions. All patients were given intravenous immunoglobulin for five days at a 400 mg/kg/day dosage, as per the protocol. Clinical outcomes were evaluated using the HFG scale at discharge and four weeks. The average patient age was 5.81 ± 3.26 years out of 30. Thirteen men (43.3%) and seventeen females (56.7%) were present. Fifteen patients (53.3%) had a history of upper respiratory illness, while seven (23.3%) had a history of gastrointestinal infection. A mean HFG score of 3.03 ±1.90 was recorded. Outcomes were good for 21 patients (56.7%) and deficient for 9 (43.3%). A tertiary care hospital in Karachi reported that 56.7% of children admitted with Guillain-Barre Syndrome had good clinical results in the intensive care unit.